Social Development of Russia’s Rural Territories: Problems and Ways of Solving Them (International Journal of Psychosocial Rehabilitation, 2020)
The sanction pressure upon the national economy was a catalyst for the development of Russia’s agriculture. Agriculture is one of the branches of Russia’s economy, in which economic growth was preserved. An increase in agricultural labor productivity led to the labor payment growth of the organization's employees, but, on the other hand, the unemployment of Russia’s rural population grew too. It is necessary to note that the labor productivity level in the branch is much lower than in a number of the economically developed countries as well as the developing countries. Apart from that, even now the labor payment level in Russia’s agriculture is lower than the average economic level. Optimization of the social expenses of the federal budget, which is performed by Russia’s government, was expressed in the mass closing down of kindergartens, schools, and clinics in villages and, as a consequence, in the forced population outflow from the small rural localities. The authors believe that the socio-economic problems of Russia’s rural territories development cannot be solved without the government’s active participation. It is necessary for the Russian government, on a systemic basis, to develop a strategy for the socio-economic development of the rural territories. The following top priority measures can be offered to create an incentive system of the highly productive labor to form a system of training and re-training of the personnel to reform the public health system 4) to supply the population with modern dwelling to reorganize the rural settlement system. In particular, it is possible to solve the problem of a high unemployment level of Russia’s rural population through diversifying rural employment. Diversification of the rural activities makes the correlation between the agricultural development and the territories social development less close. However, a systematically important role of agriculture in developing the rural territories remains unchanged.